Solid-waste-based corrosion-resistant high-ductility concrete material and preparation method thereof
By using solid waste materials to replace part of the components of high ductility concrete and optimizing the component relationship, the problem of high cost of existing high ductility concrete materials is solved, low-cost high ductility concrete material preparation is achieved, and the corrosion resistance of the material is improved.
Patent Information
- Application Number
- CN202411899476.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
AI Technical Summary
The high cost of preparation and use of existing high-ductility concrete materials has hindered its promotion in engineering applications.
By using solid waste materials such as recycled brick powder and incinerated ash to replace some existing high-ductile concrete components, and optimizing the mutual influence relationship between different components, reducing the limit dosage, solid waste-based corrosion-resistant high-ductile concrete materials are prepared.
While ensuring the ideal tensile properties of high-ductility concrete materials, it reduces the cost of preparation and use of materials, is suitable for low-cost engineering construction, and improves the corrosion resistance of materials.
Smart Images

Figure CN119707371A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a solid waste-based corrosion-resistant high-ductility concrete material and a preparation method thereof. Background Art
[0002] Reinforced concrete pipes are made of steel bars and concrete composite materials and are the most common drainage pipes. Reinforced concrete pipes have high pressure bearing capacity, but poor impermeability and general corrosion resistance. After 20 to 30 years of operation, due to lack of management and maintenance, functional defects such as scaling and deposition and structural defects such as rupture, misalignment, corrosion, and leakage may occur. A comprehensive analysis of the current status of pipelines shows that, on the one hand, the number of kilometers of newly built pipelines is still increasing each year; on the other hand, the number of pipelines with a service life of more than 20 years is also increasing rapidly, which means that the durability of a large number of pipelines will be gradually and seriously damaged; considering the above two issues, it has become an important research issue to find pipelines built with new materials to extend the life of pipelines. Zero cement concrete has excellent acid and alkali corrosion resistance, salt corrosion resistance and other properties, which can fully adapt to the environment of underground drainage pipes and break through the use range of ordinary concrete. Compared with ordinary concrete, because no cement is used and solid waste is mainly recycled, the energy consumption and carbon emissions of zero cement concrete are greatly reduced. In order to improve the brittleness of zero cement concrete, a common practice is to add polyethylene or polyvinyl alcohol fiber to toughen the matrix, and prepare high ductility zero cement concrete with an ultimate tensile strain value of more than 3%.
[0003] However, the resulting problems are high costs, high energy consumption and high carbon emissions, which greatly hinder the promotion of zero-cement concrete in engineering applications. In particular, cost is an important measurement indicator for engineering applications. Although only 2% of the volume of fiber is introduced, its cost can account for two-thirds of the total cost of concrete.
[0004] Therefore, preparing a solid waste-based corrosion-resistant and high-ductility concrete material is the key to promoting the widespread application of this green product in practical engineering. Summary of the invention
[0005] The purpose of the present invention is to overcome the defects of the prior art, provide a solid waste-based corrosion-resistant and high-ductility concrete material and a preparation method thereof, and solve the technical problem of high preparation and use costs of conventional high-ductility concrete materials in the prior art.
[0006] To achieve the above object, the present invention provides a solid waste-based corrosion-resistant and high-ductility concrete material, the raw material composition of which, by weight, comprises:
[0007] Recycled brick powder: 100-120 parts;
[0008] Incineration ash: 870-900 parts;
[0009] Silica fume: 110-120 parts;
[0010] Quartz sand: 400-450 parts;
[0011] Zero water sodium metasilicate: 110-130 parts;
[0012] Water glass: 110-130 parts;
[0013] Polyethylene fiber: 7-8 parts;
[0014] Water: 210-250 parts.
[0015] By adopting this technical solution, recycled brick powder and incineration ash are obtained by waste treatment, and some existing high-ductility concrete components are replaced by reasonable blending to participate in the production of high-ductility concrete materials. While ensuring the high-ductility concrete materials with ideal tensile properties, the preparation and use costs of high-ductility concrete materials are reduced, and they are better used in low-cost engineering construction. In addition, by optimizing the mutual influence relationship between different components, the limiting dosage involved in the production of high-ductility concrete materials is reduced, further reducing the preparation and use costs of high-ductility concrete materials.
[0016] Furthermore, the regenerated brick powder is obtained by grinding construction waste clay with a SMφ500*500mm test mill for 10 minutes, and the content of SiO2 in the main components is 40-60%, and the content of Al2O3 is 20-40%.
[0017] By adopting this technical solution, construction waste can be fully utilized to achieve waste utilization, which is both green and environmentally friendly and reduces the cost of raw materials for preparing high-ductility concrete materials. At the same time, SiO2 and Al2O3 in the recycled brick powder obtained from the treatment of construction waste can be used as stable precursors to ensure the effective production of the required polymer products in the preparation process and thus provide strength; recycled brick powder has good rheological properties, which can increase the viscosity of the high-ductility concrete slurry to improve the dispersion of fibers added in the preparation process, thereby ensuring the ductility of the subsequently prepared high-ductility concrete material after consolidation.
[0018] Furthermore, the incineration ash is obtained by incinerating municipal sewage sludge, and satisfies a 45 μm sieve residue of less than 45%. Among its main components, the content of SiO2 is 30-50%, the content of Al2O3 is 20-40%, and the content of CaO is ≤8%.
[0019] By adopting this technical solution, municipal sludge waste can be fully utilized to achieve waste utilization, which is both green and environmentally friendly and reduces the cost of raw materials for preparing high-ductility concrete materials. At the same time, SiO2 and Al2O3 in the incineration ash obtained from the treatment of municipal sludge waste can be used as stable precursors to ensure the effective production of the required polymer products in the preparation process and thus provide strength; the particle size of the incineration ash meets the 45μm sieve residue <45%, which can form a dense microstructure and thus ensure the strength of the high-ductility concrete material after consolidation; the incineration ash has good rheological properties, which can increase the viscosity of the high-ductility concrete slurry to improve the dispersion of the fibers added in the preparation process, thereby ensuring the ductility of the subsequently prepared high-ductility concrete material after consolidation.
[0020] Furthermore, the particle size of the silica fume is 0.1-1 μm, the activity index is ≥110%, and the SiO2 content of the main component is ≥95%.
[0021] By adopting this technical solution, silica fume with a particle size of 0.1 to 1 μm can be used as a micro-filler to improve the structural density of the high-ductility concrete material after consolidation, thereby improving the strength; the SiO2 content in the silica fume is ≥95%, and the activity index is ≥110%. After the silica fume is dissolved, it can provide the silicon component necessary for the product of high-ductility concrete material, adjust the silicon-aluminum ratio of the product's chemical composition, and then optimize the product structure.
[0022] Furthermore, the particle size of the quartz sand is 80 to 250 μm.
[0023] By adopting this technical solution, the conventional high-ductility concrete material has a large shrinkage rate after hardening, and quartz sand is used to provide rigid constraints to improve the shrinkage resistance of the high-ductility concrete material after hardening; quartz sand as aggregate forms an effective bond with the slurry to improve the mechanical strength of the high-ductility concrete material after consolidation; finer aggregates can reduce the fracture toughness of the matrix of the high-ductility concrete material after consolidation, promote the generation of multiple cracks, and thus help to obtain high ductility at a low fiber content.
[0024] Furthermore, the particle size of the zero-hydrate sodium metasilicate is 10 to 2000 μm, and the modulus is 0.8 to 1.0.
[0025] By adopting this technical solution, the alkalinity of zero-water sodium metasilicate is low, and the engineering application is safe. It does not release heat when in contact with water, and the process of using sodium hydroxide to prepare the activator solution in advance can be omitted. In addition to providing alkali metal ions, it can also provide the silicon component necessary for the geopolymerization reaction, thereby promoting the formation of high-ductility concrete material products.
[0026] The particle size is set between 10 and 2000 μm, and can be directly mixed with dry materials during stirring. After being dissolved in water, pores will be formed, which will help reduce the toughness of the matrix and promote high ductility at low fiber content.
[0027] Furthermore, the sodium silicate content in the main component of the water glass is ≥42%, and its modulus is 2.1-2.5.
[0028] By adopting this technical solution, water glass is added to increase the silicon modulus, so that the silicon modulus after using zero-water metasilicic acid is increased to the optimal value, which helps to generate a dense geopolymer product, thereby ensuring that the high-ductility concrete material obtains the highest compressive strength after consolidation.
[0029] Furthermore, the polyethylene fiber has a diameter of 20-24 μm, a length of 12-18 mm, an aspect ratio of >600, an elongation at break of 2-3%, and a tensile strength of 2800 MPa.
[0030] By adopting this technical solution, high-strength, high elastic modulus polyethylene fibers are selected as reinforcing materials to play a stress bridging role, and the toughening of high-ductility concrete materials is achieved through multi-crack cracking. At the same time, the expansion of cracks is limited, and the crack width is controlled to a low level below 200μm to isolate the infiltration of corrosive ions.
[0031] The present invention also provides a method for preparing a solid waste-based corrosion-resistant and high-ductility concrete material, comprising the following steps:
[0032] S1. Prepare the raw materials according to the ratio;
[0033] S2. Add the recycled brick powder, incineration ash, silica ash, quartz sand and zero-water sodium metasilicate weighed by mass into the mixer and stir for 1 to 2 minutes to make the dry powder fully mixed;
[0034] S3. Mix the water glass and water weighed by mass in advance, then add them into the mixer and continue stirring for 2 to 3 minutes to make the slurry fully mixed;
[0035] S4. Add polyethylene fiber under slow stirring and stir rapidly for 2 to 3 minutes to make the polyethylene fiber evenly dispersed;
[0036] S5. After the stirring is completed, the slurry is transferred to the mold, vibrated for 1 to 2 minutes to form, and then cured and demolded to obtain the product.
[0037] Compared with the prior art, the present invention has the following beneficial effects:
[0038] Recycled brick powder and incineration ash are obtained by waste treatment, and some existing high-ductility concrete components are replaced by reasonable blending to participate in the production of high-ductility concrete materials. While ensuring the high-ductility concrete materials with ideal tensile properties, the preparation and use costs of high-ductility concrete materials are reduced, and they are better used in low-cost engineering construction. In addition, by optimizing the mutual influence relationship between different components, the limiting dosage involved in the production of high-ductility concrete materials is reduced, further reducing the preparation and use costs of high-ductility concrete materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 This is a uniaxial tensile stress-strain diagram of the concrete material obtained in an embodiment of the present invention. DETAILED DESCRIPTION
[0040] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.
[0041] The invention provides a solid waste-based corrosion-resistant and high-ductility concrete material, which comprises, by weight, 100 to 120 parts of recycled brick powder; 870 to 900 parts of incineration ash; 110 to 120 parts of silica ash; 400 to 450 parts of quartz sand; 110 to 130 parts of zero-water sodium metasilicate; 110 to 130 parts of water glass; 7 to 8 parts of polyethylene fiber; and 210 to 250 parts of water.
[0042] Recycled brick powder and incineration ash are obtained by waste treatment, and some existing high-ductility concrete components are replaced by reasonable blending to participate in the production of high-ductility concrete materials. While ensuring the high-ductility concrete materials with ideal tensile properties, the preparation and use costs of high-ductility concrete materials are reduced, and they are better used in low-cost engineering construction. In addition, by optimizing the mutual influence relationship between different components, the limiting dosage involved in the production of high-ductility concrete materials is reduced, further reducing the preparation and use costs of high-ductility concrete materials.
[0043] Furthermore, the recycled brick powder is obtained by grinding construction waste clay with an SMφ500*500mm test mill for 10 minutes, and the content of SiO2 in the main components is 40-60%, and the content of Al2O3 is 20-40%; making full use of construction waste to achieve waste utilization is both green and environmentally friendly, and reduces the cost of raw materials for preparing high-ductility concrete materials. At the same time, SiO2 and Al2O3 in the recycled brick powder obtained by processing construction waste can be used as stable precursors to ensure the effective production of the required polymerization products in the preparation process and thus provide strength; the recycled brick powder has good rheological properties, which can improve the viscosity of the high-ductility concrete slurry to improve the dispersion of fibers added in the preparation process, thereby ensuring the ductility of the subsequently prepared high-ductility concrete material after consolidation.
[0044] Furthermore, the incineration ash is obtained from the incineration of municipal sludge, and satisfies the 45μm sieve residue <45%, and the main components thereof have a SiO2 content of 30-50%, an Al2O3 content of 20-40%, and a CaO content of ≤8%; making full use of municipal sludge waste to achieve waste utilization is both green and environmentally friendly, and reduces the cost of raw materials used in preparing high-ductility concrete materials. At the same time, SiO2 and Al2O3 in the incineration ash obtained from the treatment of municipal sludge waste can be used as stable precursors to ensure the effective production of the required polymer products in the preparation process and thus provide strength; the particle size of the incineration ash satisfies the 45μm sieve residue <45%, and a dense microstructure can be formed, thereby ensuring the strength of the high-ductility concrete material after consolidation; the incineration ash has good rheological properties, which can increase the viscosity of the high-ductility concrete slurry to improve the dispersion of the fibers added in the preparation process, thereby ensuring the ductility of the subsequently prepared high-ductility concrete material after consolidation.
[0045] Furthermore, the particle size of the silica fume is 0.1 to 1 μm. The silica fume with a particle size of 0.1 to 1 μm can be used as a microfiller to improve the structural density of the high-ductility concrete material after consolidation, thereby improving the strength; the activity index is ≥110%, and the SiO2 content in its main component is ≥95%. After the silica fume is dissolved, it can provide the silicon component necessary for the high-ductility concrete material product, adjust the silicon-aluminum ratio of the product chemical composition, and then optimize the product structure.
[0046] Furthermore, the particle size of the quartz sand is 80 to 250 μm. Conventional high-ductility concrete materials have a large shrinkage rate after hardening. Quartz sand is used to provide rigid constraints to improve the shrinkage resistance of the high-ductility concrete materials after hardening. Quartz sand is used as aggregate to form an effective bond with the slurry, thereby improving the mechanical strength of the high-ductility concrete materials after consolidation. Finer aggregates can reduce the fracture toughness of the matrix of the high-ductility concrete materials after consolidation, promote the generation of multiple cracks, and thus facilitate obtaining high ductility at a low fiber content.
[0047] The particle size of zero-water sodium metasilicate is 10-2000 μm, and its modulus is 0.8-1.0; the use of zero-water sodium metasilicate has low alkalinity and high engineering application safety; it does not release heat when in contact with water, and the process of using sodium hydroxide to prepare an activator solution in advance can be omitted; in addition to providing alkali metal ions, it can also provide silicon components necessary for geopolymerization, thereby promoting the generation of high-ductility concrete material products; the particle size is set between 10 and 2000 μm, and it can be directly mixed with dry materials during stirring, and pores will be formed after being dissolved in water, which will help reduce the toughness of the matrix and promote high ductility at low fiber content.
[0048] Furthermore, the sodium silicate content in the main component of the water glass is ≥42%, and its modulus is 2.1-2.5. The water glass is added to increase the silicon modulus, so that the silicon modulus after using zero-water metasilicic acid is increased to an optimal value, which helps to generate a dense geopolymer product, thereby ensuring that the high-ductility concrete material obtains the highest compressive strength after consolidation.
[0049] Furthermore, the polyethylene fiber has a diameter of 20 to 24 μm, a length of 12 to 18 mm, an aspect ratio of >600, an elongation at break of 2 to 3%, and a tensile strength of 2800 MPa. High-strength, high-elastic modulus polyethylene fiber is selected as a reinforcing material to play a stress bridging role, achieve toughening of high-ductility concrete materials through multi-crack cracking, and simultaneously limit the expansion of cracks, controlling the crack width to a low level of less than 200 μm to isolate the infiltration of corrosive ions.
[0050] The present invention also provides a method for preparing a solid waste-based corrosion-resistant and high-ductility concrete material, comprising the following steps: S1, preparing various raw materials according to a proportion; S2, adding recycled brick powder, incineration ash, silica ash, quartz sand, and zero-water sodium metasilicate weighed by mass into a mixer, stirring for 1 to 2 minutes, so that the dry powder is fully mixed; S3, mixing water glass and water weighed by mass in advance, and then adding them into the mixer, continuing to stir for 2 to 3 minutes, so that the slurry is fully mixed; S4, adding polyethylene fiber under slow stirring, stirring rapidly for 2 to 3 minutes, so that the polyethylene fiber is evenly dispersed; S5, after the stirring is completed, transferring the slurry to a mold, vibrating for 1 to 2 minutes to form, and then curing and demolding to obtain the product.
[0051] The following is a detailed description of an embodiment of the present invention. This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and a specific operation process are given, but the protection scope of the present invention is not limited to the following embodiment.
[0052] Unless otherwise specified, the raw materials used in the examples are all well-known, commercially available chemical raw materials.
[0053] The preparation process of the solid waste-based corrosion-resistant and high-ductility concrete material in this embodiment is as follows:
[0054] 1. Add 116 parts of recycled brick powder, 887 parts of incineration ash, 114 parts of silica fume, 419 parts of quartz sand and 120 parts of anhydrous metasilicic acid into a mixer, stir the dry powder for 1 to 2 minutes and mix well;
[0055] 2. Mix 124 parts of water glass and 220 parts of water in advance, add them into the mixer, and stir for 2 to 3 minutes to make the slurry evenly mixed;
[0056] 3. Add 7 parts of polyethylene fiber and stir thoroughly for 2 to 3 minutes;
[0057] 4. After the stirring is completed, the slurry is transferred to the mold, vibrated for 1 to 2 minutes to form, and then cured. When the product is demoulded at the specified age, it can be obtained.
[0058] The product number in this example is 1-1, and the mechanical properties test results of the obtained product are shown in Table 1:
[0059] Table 1 Test results of product mechanical properties
[0060]
[0061] The uniaxial tensile stress-strain diagram of this embodiment is shown in Figure 1 As shown, the high ductility concrete material prepared with a fiber content of 0.75% has a unidirectional tensile ductility of up to 9.398% after consolidation, and has obvious strain hardening and deformation capabilities; the high ductility concrete material prepared with a fiber content of 0.75% has an initial crack tensile strength of 3.738MPa and an ultimate tensile strength of 4.602MPa after consolidation.
[0062] Based on the high ductility concrete material obtained from the above experimental data, citric acid and lactic acid were used as the matrix to prepare a corrosion solution with a pH of 2.5 to simulate the organic acid produced by the microbial corrosion process of concrete sewage pipes to quickly evaluate the sewage corrosion resistance of the material. The experimental data are as follows:
[0063] After immersion for 84 days, the quality of traditional cement-based high-ductility concrete material (ECC) decreased significantly under the corrosion of corrosive liquid, about 4-11%, while the quality of this product changed by less than 2%; at the same time, ECC expanded significantly in the corrosive liquid, indicating that traditional cement-based materials reacted with organic acids to form volume-expanding compounds; after organic acid corrosion, the compressive strength of traditional ECC decreased by more than 15%, while that of this product decreased by less than 5%, indicating that this product has good corrosion resistance.
[0064] The present invention is described in detail above in conjunction with the embodiments of the accompanying drawings. A person skilled in the art can make various variations of the present invention according to the above description. Therefore, certain details in the embodiments should not constitute a limitation of the present invention, and the scope of protection of the present invention shall be defined by the scope of the attached claims.
Claims
1. A solid waste-based corrosion-resistant and high-ductility concrete material, characterized in that: The raw material composition by weight includes: Recycled brick powder: 100-120 parts; Incineration ash: 870-900 parts; Silica fume: 110-120 parts; Quartz sand: 400-450 parts; Zero water sodium metasilicate: 110-130 parts; Water glass: 110-130 parts; Polyethylene fiber: 7-8 parts; Water: 210-250 parts.
2. The solid waste-based corrosion-resistant and high-ductility concrete material according to claim 1, characterized in that: The regenerated brick powder is obtained by grinding construction waste clay with an SMφ500*500mm test mill for 10 minutes, and the content of SiO2 in the main components is 40-60%, and the content of Al2O3 is 20-40%.
3. The solid waste-based corrosion-resistant and high-ductility concrete material according to claim 1, characterized in that: The incineration ash is obtained by incinerating municipal sewage sludge, and satisfies the requirement that the 45 μm sieve residue is less than 45%. Among the main components, the content of SiO2 is 30-50%, the content of Al2O3 is 20-40%, and the content of CaO is ≤8%.
4. The solid waste-based corrosion-resistant and high-ductility concrete material according to claim 1, characterized in that: The particle size of the silica fume is 0.1-1 μm, the activity index is ≥110%, and the SiO2 content in the main component is ≥95%.
5. The solid waste-based corrosion-resistant and high-ductility concrete material according to claim 1, characterized in that: The particle size of the quartz sand is 80-250 μm.
6. The solid waste-based corrosion-resistant and high-ductility concrete material according to claim 1, characterized in that: The particle size of the zero-water sodium metasilicate is 10 to 2000 μm, and the modulus is 0.8 to 1.
0.
7. The solid waste-based corrosion-resistant and high-ductility concrete material according to claim 1, characterized in that: The sodium silicate content of the main component of the water glass is ≥42%, and its modulus is 2.1-2.
5.
8. The solid waste-based corrosion-resistant and high-ductility concrete material according to claim 1, characterized in that: The polyethylene fiber has a diameter of 20-24 μm, a length of 12-18 mm, an aspect ratio of more than 600, a breaking elongation of 2-3%, and a tensile strength of 2800 MPa.
9. A method for preparing the solid waste-based corrosion-resistant and high-ductility concrete material according to any one of claims 1 to 8, characterized in that: The steps include: S1. Prepare the raw materials according to the ratio; S2. Add the recycled brick powder, incineration ash, silica ash, quartz sand and zero-water sodium metasilicate weighed by mass into the mixer and stir for 1 to 2 minutes to make the dry powder fully mixed; S3. Mix the water glass and water weighed by mass in advance, then add them into the mixer and continue stirring for 2 to 3 minutes to make the slurry fully mixed; S4. Add polyethylene fiber under slow stirring and stir rapidly for 2 to 3 minutes to make the polyethylene fiber evenly dispersed; S5. After the stirring is completed, the slurry is transferred to the mold, vibrated for 1 to 2 minutes to form, and then cured and demolded to obtain the product.